2004
DOI: 10.1016/j.nimb.2004.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Low energy Ar+ ion beam induced kinetic roughening of thin Pt films on a Si substrate

Abstract: A 30 nm Pt thin film evaporated onto a Si wafer was sputtered by 8 keV Ar + ions at various ion doses. The evolution of the modified sputtered films was monitored by atomic force microscopy (AFM), high resolution scanning electron microscopy (HRSEM) and Rutherford backscattering spectrometry (RBS). The most interesting observation was the formation of mound-like structures on the metal surface. Morphological data were quantitatively analysed within the framework of the dynamic scaling theory. Analyses of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Figure D shows the optimal loading of Pd catalyst once grown and rolled-up inside the 50 μm long and 8 μm wide micromotor. It should be noted that the resulting Pd-surface morphology is highly desirable as much of the catalytic efficiency needed for hydrogen evolution via hydrolysis of NaBH 4 present in the reaction mixture is attributed to the surface roughness and support matrix of the catalyst. This was further confirmed when we observed that no propulsion effect was observed by e-beam deposited Pd layer (10 nm) over thin films (see Video S3 in SI). We were able to achieve the same by incorporating a rough surface morphology with a stable organic support for our catalytic microtubes as confirmed by XPS (see Figure S1 in Supporting Information)…”
supporting
confidence: 59%
“…Figure D shows the optimal loading of Pd catalyst once grown and rolled-up inside the 50 μm long and 8 μm wide micromotor. It should be noted that the resulting Pd-surface morphology is highly desirable as much of the catalytic efficiency needed for hydrogen evolution via hydrolysis of NaBH 4 present in the reaction mixture is attributed to the surface roughness and support matrix of the catalyst. This was further confirmed when we observed that no propulsion effect was observed by e-beam deposited Pd layer (10 nm) over thin films (see Video S3 in SI). We were able to achieve the same by incorporating a rough surface morphology with a stable organic support for our catalytic microtubes as confirmed by XPS (see Figure S1 in Supporting Information)…”
supporting
confidence: 59%
“…Low energy ion irradiation offers one possibility to modify the surface of the films. Karmakar et al [16] has shown the change in surface roughness of Pt film by Ar + ion bombardment at different ion fluence. Hydrogen absorption capability of Pd is increased after ion irradiation because of surface modification [17].…”
Section: Introductionmentioning
confidence: 99%
“…Note, however, that Chen, et al [24] bombarded Ge on Si with 300 eV Ar and Krishna, et al [25] bombarded zinc oxide films on Si(100) with 15 keV Ar , and both observed that the rms roughness and the diameter of the clusters decrease with ion fluence similar to the results reported here. Interestingly, nanodots of Si on Si [26] and Pt nanostructures on Si [27] produced by ion sputtering also decrease their dimensions with further sputtering. The existing theory predicts that the rms roughness would initially increase and saturate after a certain time t x , called the crossover time.…”
mentioning
confidence: 99%